A Comparative Evaluation of Post-Operative Pain and Function after Gingival Depigmentation Using 940 Nm Diode Laser And Conventional Bur Method: 6 Months Study - Sukker, Mahdi A. (Iraqi Journal of Laser, 2017)
The aim of the study was to evaluate the efficacy of diode laser (λ=940 nm) in the management of gingival hyperpigmentation compared to the conventional bur method. Materials and methods: Eighteen patients with gingival hyperpigmentation were selected for the study with an age between 12-37 years old. The site of treatment was the upper gingiva using diode laser for the right half and the conventional method for the left half. All patients were re-evaluated after the following intervals: 3 days, 7 days, 1 month and 6 months post-operation. Pain and functions were re-evaluated in each visit for a period of 1 day, 3 days and 1 week post-operation. Laser parameters included 1.5 W in continuous mode with an initiated tip (400 μm) placed in contact with tissues and Power density (irradiance) was 1250 W/cm2. Results: A significant difference was observed in post-operation pain and functions between the groups (Level of significance as: Not significant P>0.05 and Significant P